What Can Be Done to Improve the Mental Health of University Students? Identifying Determinants of Psychological Distress at an Australian University - Patrick J. Owen; Shane A. Kavanagh; Anthony D. LaMontagne (JANZSSA)
Background: Mental health problems are common among university students. This study examined associations between determinants of mental health and psychological distress among university students with the aim of identifying priorities for policy and practice action.